Co-Teaching for E-Portfolio Implementation in Teacher Education: A PALAR Study from a South African University of Technology - Brigitte Lenong; Paseka Mollo (Universitas Majalengka, 2026)
This reflective piece examines the benefits and challenges lecturers face in implementing participatory action learning and action research (PALAR) e-portfolios at the University of Technology. While e-portfolios aim to enhance learning in higher education, research on the implementation of co-teaching through the PALAR process is limited. This qualitative study engaged six purposefully selected lecturers in reflecting on the integration of e-portfolios in teacher education. PALAR functioned as both a theoretical framework and methodological approach for data collection and analysis. Thematic analysis revealed that PALAR fosters lecturers' professional growth, transformative learning, and collaborative teaching practices. While effective co-teaching enriched reflective practices and student outcomes, challenges arose in co-planning, co-facilitating, and co-assessing e-portfolios. The findings underline the importance of interconnected factors for effective e-portfolio implementation in higher education, especially in collaborative settings using PALAR. The study recommends adapting PALAR for co-teaching to refine practices in higher education, emphasizing the need for active involvement from both lecturers and management in implementing a strategic approach to technology use.